2023
DOI: 10.1029/2023gl106131
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Distant Magnetopause Locations Caused by Magnetosheath Jets

Z. Němeček,
J. Šafránková,
K. Grygorov
et al.

Abstract: Magnetopause position is controlled mainly by the solar wind dynamic pressure and north‐south interplanetary magnetic field component and these quantities are included in different empirical magnetopause models. We have collected about 50,000 of dayside magnetopause crossings observed by THEMIS in course of 2007–2019 and compared the observed magnetopause position with model prediction. The difference between observed and predicted magnetopause radial distance, Robs − Rmod is used for quantifying the model‐obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…"J1" impacts the magnetopause along the normal direction of the magnetopause, causing a localized magnetopause indentation. The magnetopause is dented more severely as "J1" continuously compresses the magnetopause in later times and expands back beyond its original location (not shown), as suggested by Němeček et al (2023). Moreover, "J1" is meandering in the cyan slice (Figures 2c and 2e), which may be caused by Kelvin-Helmholtz instability (Guo et al, 2022).…”
Section: Simulation Resultsmentioning
confidence: 88%
“…"J1" impacts the magnetopause along the normal direction of the magnetopause, causing a localized magnetopause indentation. The magnetopause is dented more severely as "J1" continuously compresses the magnetopause in later times and expands back beyond its original location (not shown), as suggested by Němeček et al (2023). Moreover, "J1" is meandering in the cyan slice (Figures 2c and 2e), which may be caused by Kelvin-Helmholtz instability (Guo et al, 2022).…”
Section: Simulation Resultsmentioning
confidence: 88%
“…Furthermore, it has been observed that the high-latitude magnetopause distance around the cusp regions is significantly different from that near the ecliptic, leading to the formation of cusp indentations (Boardsen et al, 2000;Safrankova and Dusik, 2005;Wang et al, 2013). Additionally, the radial component of the IMF is apparently important, as larger magnetopause distances have been noted during periods of radial IMF (Merka et al, 2003;Dušík et al, 2010;Samsonov et al, 2012;Park et al, 2016;Němeček et al, 2023).…”
Section: Introductionmentioning
confidence: 99%